1994
DOI: 10.1161/01.atv.14.7.1223
|View full text |Cite
|
Sign up to set email alerts
|

Elastic modulus of the radial artery wall material is not increased in patients with essential hypertension.

Abstract: Hypertension is known to decrease arterial distensibility and systemic compliance. However, the arterial tree is not homogeneous, and it has been shown that the mediumsize radial artery does not behave like the proximal, elastic, large, common carotid artery. Indeed, radial artery compliance in hypertensive patients (HTs) has been shown to be paradoxically increased when compared with that in normotensive control subjects (NTs) at the same blood pressure level. To determine whether this increase was due to hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
149
0
2

Year Published

1998
1998
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 202 publications
(159 citation statements)
references
References 40 publications
8
149
0
2
Order By: Relevance
“…This measure is independent of the actual BP in normotensive subjects (18,19). Finally, the incremental modulus of elasticity (E inc ) provides direct information about the arterial wall material, independent of its geometry (20). We found low arterial wall distensibility, a high arterial stiffness parameter, and a high incremental modulus of elasticity in all patients compared with age-matched and gender matched healthy controls.…”
Section: Discussionmentioning
confidence: 73%
“…This measure is independent of the actual BP in normotensive subjects (18,19). Finally, the incremental modulus of elasticity (E inc ) provides direct information about the arterial wall material, independent of its geometry (20). We found low arterial wall distensibility, a high arterial stiffness parameter, and a high incremental modulus of elasticity in all patients compared with age-matched and gender matched healthy controls.…”
Section: Discussionmentioning
confidence: 73%
“…22,23 The effects of sympathetic stimulation on arterial mechanical properties are complex and depend on passive effects of the increased arterial pressure and of changes in vessel geometry and smooth muscle tone due to active vasoconstriction. Increasing blood pressure stretches vessel walls and reduces their compliance by increasing wall stiffness (represented by the incremental modulus) and the radius-to-wall thickness ratio.…”
Section: Discussionmentioning
confidence: 99%
“…2,11 Recent studies indicate that differences in distending pressure account for arterial stiffness in essential hypertension. 18,19 Laurent et al 19 have shown that the decrease in arterial distensibility was primarily due to higher distending BP rather than to structural modifications, and when adjusted for differences in BP, hypertrophied arteries of essential hypertensive subjects were more distensible than those of normotensive controls. In contrast to the results in essential hypertensive subjects, arterial stiffness in hypertensive patients with end-stage renal failure appear to be related to structural vessel wall changes.…”
Section: Discussionmentioning
confidence: 99%